Culinary potential based on local food in the cultural tourism of Pacet's Keramat Market - Anita Anita; Nuril Ahmad; Eko Sutrisno; Rakhmad Wahyudi (Borneo Novelty Publishing, 2025)
Purpose - The purpose of this study is to identify the potential of food made from local resources, specifically sweet potatoes, as a support for cultural tourism in the Keramat market. It also aims to modify sweet potato recipes to make them more innovative and aligned with modern tastes.Methodology/Design/Approach - This is descriptive qualitative research. Data was collected through interviews, Focus Group Discussions (FGD), and experiments involving the modification of sweet potato-based foods. A total of 30 seller respondents were purposively selected to participate in the study. Finding - The study found that the most commonly sold sweet potato-based foods were cenil (16.67% of sellers), followed by gatot and tiwul (13.33%), puthu (13.33%), sundhuk urut (13.33%), dawet drinks (10%), horok-horok (6.68%), and other products like corn, sweet potatoes, and boiled peanuts (3.33%). The study also identified that local resources, specifically sweet potatoes from Pacet, could support cultural tourism by modifying them into modern dishes such as silky sweet potato pudding and sweet potato mayang cake. These dishes incorporate additional ingredients like coconut milk and milk to enhance the nutritional value.Originality/Value - The research highlights the potential of modifying traditional food products to support cultural tourism. By transforming local sweet potato-based foods into innovative dishes, the study provides a unique approach to integrating local resources into tourism and cultural experiences, offering fresh ideas for culinary tourism development.